2003
DOI: 10.1007/s00595-003-2566-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Intrathoracic Mesenterioaxial Volvulus of the Stomach in an Adult: Report of a Case

Abstract: Intrathoracic gastric volvulus is an uncommon entity, in which the stomach undergoes organoaxial torsion occurring in the chest due to the concomitant presence of an enlargement of the hiatus. We herein report an unusual case of acute intrathoracic mesenterioaxial volvulus of the stomach. Gastric rotation occurred at the transverse axis and the mobile pylorus herniated in the chest through a large hiatal defect. Following a reduction of the volvulus through the use of a nasogastric tube, the patient underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…C Postoperative barium esophagram. D Postoperative endoscopic fi ndings showed disappearance of esophagitis chronic changes in symptoms are frequently observed, as in our patients, and the passage from the cardia to the upper part of the stomach is well preserved [5]. Endoscopic repositioning is successfully performed in isolated patients.…”
Section: Discussionmentioning
confidence: 77%
“…C Postoperative barium esophagram. D Postoperative endoscopic fi ndings showed disappearance of esophagitis chronic changes in symptoms are frequently observed, as in our patients, and the passage from the cardia to the upper part of the stomach is well preserved [5]. Endoscopic repositioning is successfully performed in isolated patients.…”
Section: Discussionmentioning
confidence: 77%
“…Although the numbers are small, this finding suggests that laparoscopic repair may be a feasible option for the treatment of PEH with associated gastric volvulus; this has been reported in other studies. (29,30) A more recent study by Teague et al also showed good results with no mortality in all of their 36 patients, five of which had chronic volvulus that were treated conservatively. (31) It is worth noting that, even though PEH is a rare condition in Asian populations and experience with PEH is limited, there were no mortalities in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…This entity occurs when the stomach rotates into an abnormal position within the chest through the diaphragmatic defect. Increased intraabdominal pressure can then lead to lifethreatening gastric strangulation [27][28][29]. A delay in the diagnosis and treatment may result in fatal consequences.…”
mentioning
confidence: 99%